The sea keeper's daughters ebook - Wingate, Lisa (Carolina Heirlooms, 2015)
From the #1 New York Times bestselling author of Before We Were Yours. From modern-day Roanoke Island to the sweeping backdrop of North Carolina’s Blue Ridge Mountains and Roosevelt’s WPA folklore writers, past and present intertwine to create an unexpected destiny. Restaurant owner Whitney Monroe is desperate to save her business from a hostile takeover. The inheritance of a decaying Gilded Age hotel on North Carolina’s Outer Banks may provide just the ray of hope she needs. But things at the Excelsior are more complicated than they seem. Whitney’s estranged stepfather is entrenched on the third floor, and the downstairs tenants are determined to save the historic building. Searching through years of stored family heirlooms may be Whitney’s only hope of quick cash, but will the discovery of an old necklace and a Depression-era love story change everything? Beautiful and heartfelt with themes of family, forgiveness, and hope Features clean, sweet romance Includes discussion questions for book clubs